Computer busses design and application - Buchanan, William (Boca Raton : CRC, 2000)
As more and more equipment is interface or'bus' driven, either by the use of controllers or directly from PCs, the question of which bus to use is becoming increasingly important both in industry and in the office. 'Computer Busses' has been designed to help choose the best type of bus for the particular application. There are several books which cover individual busses, but none which provide a complete guide to computer busses. The author provides a basic theory of busses and draws examples and applications from real bus case studies. Busses are analysed using from a top-down approach, helping the undergraduate electrical or computer engineer to chose the right type of bus for their particular application. This book is essential reading for students of software engineering and electronic design, as well as for those working in disciplines such as production engineering or process control. It will also be a handy reference book for professional engineers, systems designers, consultants and those working in technical support. Provides a complete guide to computer busses Contains application-specific programme examples Plenty of real-life case studies.
Busses, interrupts and PC systems * Interfacing standards * PCI Bus * Motherboard design * IDE and mass storage * SCSI * PCMCIA * USB*Firewire * Games port, keyboard and mouse * AGP * Fiber channel * RS-232 * RS-422*RS-423*RS-485 * Modems * Parallel port * Enhanced parallel port * Modbus * Fieldbus * Worldfip * CAN Bus * IEEE-488*VME*VXI * TCP*IP * TCP*UDP * Networks * Ethernet * RS-232 Programming (Visual Basic) * Interrupt-driven RS-232 * Appendices.
Keywords: Microcomputers -- Buses; Computer interfaces; Electronic books